Fetal and Maternal Outcome in Women with Placenta Accreta - Aqusa Baloch, Romana Qaimkhani, Muhammad Siddique Rajput, Saira Talpur, Humera Yaseen, Mehreen Memon, Abrar Ahmed Qaimkhani, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of fetal and maternal outcome in women with placenta accrete presenting at Liaquat University Hospital Hyderabad / Jamshoro. Materials and Methods: Descriptive Cross sectional conducted at Department of Obstetrics and Gynaecology Liaquat University Hospital Hyderabad for Six months (January 2021 to July 2021). A total of 148 relevant ladies with placenta accreta were recruited and entered in the study and were explored for fetal outcome and maternal outcome. All the maneuvers was performed. The data was collected on pre-designed questionnaire. Results: Study participant’s average age was 26.07±4.49 years. In our study, maternal outcome were history of previous cesarean section (33.1%), emergency surgery (58.1%), elective surgery (41.9%) cesarean hysterectomy (54.1%), urinary tract injuries (19.9), received blood transfusion (79.1%), maternity high dependency unit - HDU admission (61.5%), ICU admission (31.8%) and prolonged hospital stay (59.5%) and hemorrhage (14.2%) while the fetal outcome includes low birth weight (41.2%), preterm births (50%), NICU admission (52%), low APGAR score (<7at 5 min) (29.7%), and neonatal hypoxia (9.5%) respectively. Conclusion: To counter the increased risk of maternal morbidity or mortality, placenta accreta should be confiscated in every single case of placenta previa, especially in those with previous history of uterine surgery, high parity, and advanced maternal age as risk. Proper arrangement should be made for planned delivery by trained placenta accreta team in tertiary care hospitals where all required facilities available to manage morbidly adherent placenta. Keywords: Placenta Accreta, Aqusa Baloch, Maternal and Fetal Outcome,